Attitudes of Medical Students towards Conflict of Interest: A National Survey in France - Etain, Bruno (Public Library of Science, 2014)
Following recent health scandals in France, the French parliament adopted law n°2011-2012 to regulate ties between physicians and the pharmaceutical industry. The law also requires pharmaceutical companies to publicize financial and other benefits given to medical students. In this context, we administered a survey to medical students in France, in an effort to identify priorities for future education regarding conflicts of interest (COI). This web-based survey encompassed knowledge about, training on, personal exposure to, and opinions on COI among preclinical and clinical students as well as residents. Two thousand one hundred and one (2,101) students participated. Although most students (64.6%) believed that they are able to define what a COI is, they failed to correctly identify several situations as COI (receiving a gift, being offered a meal, being invited to a conference). Most students reported feeling inadequately educated about COI (85.2%). Compared to other class levels, residents were more exposed to pharmaceutical sales representatives. This exposure is highly associated to receipt of gifts (OR 14.51, 95% CI 11.67–18.05). Medical students were aware of potential bias induced by COI with respect to drug prescriptions and research, but felt personally immune towards COI. In our survey, personal research performed by students was more likely to be associated with perception of potential bias on prescription for self (but not for others) than attending a lecture on COI. Promulgating laws that regulate ties between physicians/students and the pharmaceutical industry is a mandatory first step. However, complementary strategies should be implemented within medical schools, in particular, specific training about COI in early medical education.